Circulation pattern in the equatorial stratosphere and its relation with the circulations in the mesosphere and upper troposphere -Part I - GEORGE, P. A.; NARAYANAN, V. (MAUSAM, 1975)
The zonal circulations in the equatorial stratosphere and mesosphere over the Indian Ocean region undergo cyclic oscillations having varying degrees of periodicity. The oscillation is biennial in the middle stratosphere (25-35 km) where westerlies interrupt the prevailing easterlies in alternate years. The period of one cycle of westerlies and easterlies decrease gradually, towards higher as well as lower levels, becoming semi-annual in the lower mesosphere and annual in the upper troposphere. The lower stratosphere is characterised by a thin stream of westerlies meandering around the globe within about 10" on either sides of the equator. Because of the seasonal north-south bodily shift of the entire stream, the person westerlies exist over Trivandrum only for about 8 months of the year. During this period the upper tropospheric easterly jet would be completely absent. Although the stratosphere is considered as a very stable region with the stratopause acting as a lid over it, the strato-mesospheric circulations are found to have some influence on the tropospheric monsoonal circulations.